Looking for the good in times of adversity: examining the interplay of temperament and social schemas in shaping resilience in youth - Joosten, Frankie; Bakker, Jindra; Daemen, Maud; Amelsvoort, Therese van; Reininghaus, Ulrich (Early intervention in psychiatry, 2024)
Aim Resilience is a broad and dynamic concept that can be seen as being constituted by the combination of internal factors, for example, temperament profiles, and external factors, for example, social support. This paper aimed to identify temperament profiles in help-seeking youth exposed to adverse childhood experiences, and to investigate whether temperament (putative internal protective factor) interacts with social schemas (as proxy for the putative external protective factor social support) such that their combination is associated with (a) reduced mental health problems and (b) attenuated decrease in positive affect following daily life stressors. Methods Self-report questionnaires were used to measure temperament, social schemas and mental health problems. The experience sampling method was used to assess stress and positive affect (i.e., stress-sensitivity as a potential daily life resilience mechanism). Temperament profiles were identified by latent profile analysis and regression analyses were used to examine (interaction) effects. Results In 138 subjects, three temperament profiles were identified, that is, a moderate, volatile and persevering profile, of which the latter was negatively associated with mental health problems. Neither mental health problems nor stress sensitivity were found to be affected by the interaction between temperament and social schemas. However, positive social schemas were found to be independently associated with reduced mental health problems (b = −4.41; p = <.001) and reduced stress sensitivity (b = .10, p = .044). Conclusions Findings are relevant for both practice and research, and contribute to improving our understanding of putative protective factor in the development of mental ill-health, thereby further unravelling the construct of resilience.
Online veröffentlicht: 20. April 2024
Gesehen am 27.09.2024